Implementation of Khiyar Ta'yin in Online Flash Sale Product Purchase Transactions - Hikmah, Saripatul; Sofyan, Akhmad; Fillah, Muchammad Machbub (Islamic Economic Law Study Program, Faculty of Sharia Sultan Aji Muhammad Idris Samarinda Islamic State University, 2023)
The khiyar right that provides specific information related to similar products but different in quality is khiyar ta'yin. In practice, in purchasing flash sale products in the TikTok Shop marketplace, there are comments and testimonial columns contain various consumer experiences related to the products they have previously purchased, in the comments and testimonial columns there are also reviews related to product information both in terms of quality and so on, but many consumers who use testimonials and comments as a reference feel cheated in terms of product quality because it does not match the contents of the information provided in the testimonial reviews and comments on the TikTok Shop marketplace. With the formulation of the problem, namely first, how is the implementation of khiyar ta'yin in online flash sale product purchase transactions on the TikTok Shop marketplace according to the review of muamalah fiqh, second, how do Sharia Faculty students view testimonials and user comments as a reference in finding product information to be purchased. The purpose of the research is to find out the implementation of khiyar ta'yin in online flash sale product purchase transactions on the TikTok Shop marketplace according to muamalah fiqh review, and to find out the views of Sharia Faculty students on testimonials and user comments as a reference in finding product information to be purchased by consumers.This research uses qualitative research with an empirical normative approach, with primary data sources, namely the results of interviews with 20 students of the Faculty of Sharia UIN Sultan Aji Muhammad Idris Samarinda and secondary data consisting of the book of Fikih Muamalah, Kitab Bulughul Maram, and Kitab tafsir Ibn Kathir, journals, scientific articles, and other scientific works. The data were obtained from observations, interviews, and documentation, then the author analysed the data with descriptive qualitative methods.The results showed that the implementation of khiyar ta'yin in flash sale product purchase transactions on the TikTok Shop marketplace is not fully in accordance with fiqh muamalah because traders and buyers do not know about khiyar ta'yin so that the form of implementation of khiyar ta'yin carried out by sellers and buyers occurs by itself with business ethics to achieve benefits in the form of an element of willingness between traders and . and from the results of the interview there are still several cases of consumers who feel cheated, so from this product description, testimonials and comments there is still an element of gharar in it and can cause mafsadah to other consumers, And from the results of the interviews there are still several cases of consumers who feel cheated, so departing from this product description, testimonials and comments there is still an element of gharar in it and can cause mafsadah to other consumers.